"Of age – off school": sexual maturation, girls' education and capabilities. Issue 3 (1st April 2019) - Ogamba, Ikedinachi K.
Abstract : Purpose: Over the years, efforts to ensure equal participation of girls in school in Nigeria have been met with some setbacks, amidst significant progress in mobilising communities for gender equality and mainstreaming. The purpose of this paper is to explore a number of features associated with sexual maturation that affect girls' non-enrolment, limited attendance, performance at school and gender inequality in primary and secondary education in Nigeria. Design/methodology/approach: The analytical engagement with the capability approach draws out elements of inequalities and demonstrates that issues of sexual maturation do not just constitute personal health challenge for adolescent girls, but bring up wider issues of socio-cultural, community and institutional deprivation and injustice. Findings: Though laudable initiatives have been in place to improve girls' participation and attainment in education, there is a dire need for appropriate policy and actions to address the supply and demand barriers to meeting girls' needs, including making schools more girl-friendly and safe, providing school-based health programmes, sex education and sanitation facilities, train teachers against gender-stereotype, flexible school schedules and enforce re-admission policy. But beyond school policy and environment, there is also the need to respond to opportunity costs of schooling and leverage collective capabilities. Originality/value: This paper argues that cultural and socioeconomic factors surrounding sexual maturation are implicated in gender differentials in participation and performance of girls and gender inequality in education. It suggests the need for the application of collective capabilities for action towards addressing girls' sexual maturation issues and education in the society.